2024
DOI: 10.3389/fmicb.2024.1349016
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up construction and screening of algae-bacteria consortia for pollutant biodegradation

Zongting Cai,
Esther Karunakaran,
Jagroop Pandhal

Abstract: Microbial communities have been used as important biological tools for a variety of purposes associated with agriculture, the food industry and human health. Artificial engineering of microbial communities is an emerging field of research motivated by finding stable and efficient microbial systems. However, the successful design of microbial communities with desirable functions not only requires profound understanding of microbial activities, but also needs efficient approaches to piece together the known micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…vulgaris and some bacterial strains [ 106 ]. Recently, Cai et al [ 107 ] also showed high performance in volatile organic carbon degradation and accumulation of algal biomass by microalgae-bacteria consortia.…”
Section: The Interaction Application and Optimization Of Microalgae-b...mentioning
confidence: 99%
“…vulgaris and some bacterial strains [ 106 ]. Recently, Cai et al [ 107 ] also showed high performance in volatile organic carbon degradation and accumulation of algal biomass by microalgae-bacteria consortia.…”
Section: The Interaction Application and Optimization Of Microalgae-b...mentioning
confidence: 99%